Examining nirogacestat for adults with progressing desmoid tumors who require systemic treatment - Campos, Fernando; Kasper, Bernd (Expert opinion on pharmacotherapy, 2024)
Desmoid tumor (DT) is a rare, locally aggressive, mesenchymal neoplasm that can arise at any site in the body. Medical therapies play a major role for DT’s patients requiring treatment. A novel systemic approach has recently emerged with Nirogacestat, a γ-secretase inhibitor targeting the NOTCH signaling pathway. Nirogacestat is the first drug in its class to receive approval from the Food and Drug Administration (FDA) and is the first FDA-approved treatment specifically for DTs. We reviewed the data leading to its discovery, including its mechanism of action, pharmacological properties, clinical efficacy, and its positioning within the current treatment armamentarium for DTs. High-quality evidence for systemic therapies in the management of DTs remains an unmet need. Nirogacestat now joins sorafenib as the only drugs with efficacy in DTs demonstrated by randomized phase 3 studies. Currently, there are no comparative trials of the available systemic therapies. Therefore, physicians should consider factors such as drug accessibility, cost, toxicity profile, comorbidities, and patient preferences when selecting treatment. Long-term efficacy and safety data will be essential for evaluating the duration of treatment response and monitoring late-onset side effects of Nirogacestat.
Gesehen am 29.04.2025